Influenza related hospitalisations in Sydney, New South Wales, Australia. Issue 1 (20th December 2005) - Beard, F; McIntyre, P; Gidding, H; Watson, M
Abstract : Background: Routine influenza vaccination for children aged 6–23 months has recently been recommended in the United States. Accurate assessment of influenza related burden of illness in children could support similar recommendations in other settings. However, routinely available data underestimate the role of influenza in causing hospitalisation, and indirect estimation methods face difficulties controlling for the concurrent circulation of respiratory syncytial virus (RSV). Recent studies from Hong Kong and the United States have used differing methods to estimate the true burden of influenza related hospitalisation, with disparate results. Methods: Retrospective population based study of children less than 18 years of age from Sydney, Australia, 1994 to 2001. Using two previously reported methods, estimates of annual hospitalisation rates attributable to influenza were derived by comparison of mean hospitalisation rates for acute respiratory disease during periods of high influenza activity and low RSV activity (defined using virological surveillance data) and periods where both influenza and RSV activity were low. These estimates were compared to rates of hospitalisation where influenza was recorded as the principal discharge diagnosis. Results: Hospitalisation rates attributable to influenza were up to 11 times higher, depending on the age group and method used, compared to rates calculated from principal discharge diagnosis codes. Conclusions: Although there remains considerable uncertainty in estimating influenza related morbidity by methods using excess hospitalisations, even minimum estimates of disease burden warrant consideration of routine influenza immunisation for all children less than 2 years of age. Such estimates, derived from principal discharge diagnosis codes, are available in most settings.